Cerebrovascular carbon dioxide reactivity and failure of autoregulation in preterm infants. Issue 7 (July 1992) - Fenton, A C; Woods, K L; Evans, D H; Levene, M I
Abstract : Changes in cerebral blood flow velocity (CBFV) in response to a rise in arterial carbon dioxide tension (PaCO2) in 94 ventilated preterm infants were determined using Doppler ultrasound to assess whether the nature of this change might predict subsequent neurological injury. Concomitant changes in mean arterial pressure (MAP) were recorded. Both CBFV and MAP rose significantly in response to the rise in PaCO2, the response being significantly less in the first 24 hours. Analysis indicated that the change in CBFV in the first day of life in infants less than or equal to 30 weeks' gestation was dependent to a great extent on the concomitant change in MAP. Similar dependence also occurred after administration of pancuronium to infants whose CBFV response was previously independent of changes in MAP. This dependency lasted for the duration of paralysis. Changes in CBFV after a rise in PaCO2 did not predict subsequent neurological injury. The influence of pancuronium on cerebrovascular regulation warrants further study.